(untitled) (Research, Society and Development, 2016)
The present article refers to a exploratory study of bibliographical revision that had as objective identifies different meanings about the concepts of creativity and creative processes, including the thought of some authors that stand out in that study area, especially Ellis Paul Torrance (1976), Fayga Ostower (2013) e M. I. Majmutov (1983). Among mentioned them approaches found some similarities and other differences, tends in view the position and the study area of each one of them. Torrance, for example, approach the creativity of the point of view of the instruments, of the measures, of the tests and of the evaluations. Both emphasize relative aspects to the potentiating or inhibition in the individuals. The approach of Ostower looking for to identify the relationship among the creativity concept and the creative processes with the individual’s experience life. Majmutov presents the creativity about the highest point of the individual’s cognitive development, detaching the process of problematizer teaching as a primordial factor in the development of that thought level.